2016
DOI: 10.3389/fpsyg.2016.00547
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Seeking Professional Psychological Help: Factor Structure and Socio-Demographic Predictors

Abstract: Attitudes toward seeking professional psychological help (ATSPPH) are complex. Help seeking preferences are influenced by various attitudinal and socio-demographic factors and can often result in unmet needs, treatment gaps, and delays in help-seeking. The aims of the current study were to explore the factor structure of the ATSPPH short form (-SF) scale and determine whether any significant socio-demographic differences exist in terms of help-seeking attitudes. Data were extracted from a population-based surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
95
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 67 publications
10
95
2
12
Order By: Relevance
“…Similar to our finding that older persons were more willing to seek psychiatric help, a study from Ethiopia 18 showed that individuals aged 31-40 were about 10 times more likely to seek treatment than subjects under 20 years, which may be explained by the fact that older adults tend to have more knowledge about mental illness. However, a survey conducted in Singapore, reported that younger age was significantly associated with willingness to seek professional help 19 . There is still no conclusive evidence on the association between age and seeking psychological help.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our finding that older persons were more willing to seek psychiatric help, a study from Ethiopia 18 showed that individuals aged 31-40 were about 10 times more likely to seek treatment than subjects under 20 years, which may be explained by the fact that older adults tend to have more knowledge about mental illness. However, a survey conducted in Singapore, reported that younger age was significantly associated with willingness to seek professional help 19 . There is still no conclusive evidence on the association between age and seeking psychological help.…”
Section: Discussionmentioning
confidence: 99%
“…Being unmarried, unemployed, and being a student were associated with less prejudice and misconception towards those with mental illness; while having a monthly income less than SGD 2,000 predicted more prejudice and misconception. Marital status is usually related to age, with younger adults being less likely to be married [25]; this also applies to individuals who were students. In this sense, the association between being unmarried or a student and ‘prejudice and misconception’ might be simply caused by the effect of age.…”
Section: Discussionmentioning
confidence: 99%
“…Minor changes were made to the questions based on the cognitive interview findings; this was to ensure the items of the instrument would be understood in the manner they were intended to be and to avoid potential misinterpretation. More information on this process is available in a previous publication [25]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, items with a factor loading lower than 0.40 were eliminated from our measurement scales [48]. This practice has been commonly used in prior psychology research [49,50]. The measurement items are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%